Evidence-based management of COVID-19 in cancer patients: guideline by the Infectious Diseases Working Party (AGIHO) of the German Society for Haematology and Medical Oncology (DGHO) - Giesen, Nicola; Sprute, Rosanne; Rüthrich, Maria Madeleine; Khodamoradi, Yascha; Mellinghoff, Sibylle Christiane; Beutel, Gernot; Lück, Catherina; Koldehoff, Michael; Hentrich, Marcus; Sandherr, Michael; Bergwelt, Michael von; Wolf, Hans-Heinrich; et al. (European journal of cancer, 2020)
Since its first detection in China in late 2019 the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated infectious disease COVID-19 continue to have a major impact on global healthcare and clinical practice. Cancer patients, in particular those with haematological malignancies, seem to be at an increased risk for a severe course of infection. Deliberations to avoid or defer potentially immunosuppressive therapies in these patients need to be balanced against the overarching goal of providing optimal antineoplastic treatment. This poses a unique challenge to treating physicians. This guideline provides evidence-based recommendations regarding prevention, diagnostics and treatment of SARS-CoV-2 infection and COVID-19 as well as strategies towards safe antineoplastic care during the COVID-19 pandemic. It was prepared by the Infectious Diseases Working Party (AGIHO) of the German Society for Haematology and Medical Oncology (DGHO) by critically reviewing the currently available data on SARS-CoV-2 and COVID-19 in cancer patients applying evidence-based medicine criteria.
Gesehen am 21.01.2020